Molecular Biomethods Handbook - Walker, John M.; Rapley, Ralph (Humana Press, 2008)
Recent advances in the biosciences have led to a range of powerful new technologies, particularly nucleic acid, protein and cell-based methodologies. The most recent insights have come to affect how scientists investigate and define cellular processes at the molecular level. Molecular Biomethods Handbook, 2nd Edition expands upon the techniques included in the first edition, providing theory, outlines of practical procedures, and applications for a range of techniques. Part A of the book describes nucleic acid methods, such as gene expression profiling, microarray analysis and quantitative PCR. In Part B, protein and cell-based methods are outlined, in subjects ranging from protein engineering to high throughput screening. Written by a well-established panel of research scientists, Molecular Biomethods Handbook, 2nd Edition provides an up-to-date collection of methods used regularly in the authors’ own research programs. This book will prove to be an invaluable reference for those engaged in or entering the field of molecular biology, and will provide the necessary background for those interested in setting up and using the latest molecular techniques